Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Perseroan Terbatas Perusahaan Listrik Negara (Persero) Pembangkitan Sumatera Bagian Utara - Herna Fourtunela Br Sembiring; Patar Marbun (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2021)
The Influence of Leadership Style and Work Discipline on Employee Performance at PT PLN (Persero) Pembangkitan North Sumatra. This study aims to determine the leadership style of employee performance and work discipline on performance at PT PLN (Persero) Pembangkitan Sumaetra Utara. The sample used in this study were 59 respondents using a questionnaire. The technical analysis in this study uses hypothesis testing, descriptive analysis and multiple linear regression analysis. The results of this study are (1) leadership style has a significant positive effect on employee performance at PT PLN (Persero) Pembangkitan Sumatera Utara where it is obtained from the value of tcount 2.168 ttable 1.99897 and p-value 0.035 0.05. (2) work discipline has a significant positive effect on employee performance at PT PLN (Persero) Pembangkitan Sumatera Utara where it is obtained from the value of tcount 3.104 ttable 1.99897 and p-value 0.003 0.05. (3) leadership style and work discipline together have a significant positive effect on employee performance at PT PLN (Persero) Pembangkitan Sumatera